A novel thermal management system for a cylindrical battery based on tubular thermoelectric generator - Zhou, Xiao; M Abed, Azher; Chaturvedi, Rishabh; Abdullaeva, Barno Sayfutdinovna; Shawabkeh, Ali; Fouad, Yasser; Riaz, Fahid (Case studies in thermal engineering, 2024)
This study introduces an innovative thermal management system tailored for cylindrical Lithium-ion batteries. It integrates a tubular thermoelectric generator (TTEG) to handle both battery thermal management and the utilization of waste heat for power generation. The main focus lies in evaluating the waste heat recovery capabilities of the TTEG to enhance effective thermal management. The research investigates key geometric and operational parameters such as battery discharge rate (C-rate), thermocouple count (NTC), heat transfer coefficient (HTC), and thermoelectric leg height (HL) to comprehensively assess the overall system performance. The results highlight that integrating the TTEG improves thermal management and waste heat recovery in lithium-ion batteries. It demonstrates temperature reductions of up to 21 °C at a discharge rate of 3C compared to batteries without the TTEG thermal management system. Additionally, increasing the NTC leads to a rise in the maximum battery temperature, thereby enhancing waste heat recovery performance. For instance, increasing the number of thermocouples from 100 to 144 results in a substantial up to 70 % increase in TTEG voltage.Furthermore, enhancing HTC and HL positively impacts thermal performance, showing a significant decrease in the maximum battery temperature. Elevated HTC and HL also contribute to improving thermoelectric voltage, power, and conversion efficiency, highlighting their dual role in enhancing waste heat recovery. For instance, at peak conditions, there is a notable reduction of 2.66 °C in the maximum battery temperature with an HL of 12 mm compared to 4 mm. Additionally, increasing HTC from 10 to 20, particularly at maximum discharge, leads to a surge of 15.87 % in voltage and a substantial 34.28 % increase in output power.